Implementasi Kurikulum 2013 dan Kurikulum Merdeka Belajar di SDN 1 Ngawonggo Kecamatan Tajinan - Roudhotun Nadhifah (Universitas Negeri Malang, 2023)
Abstract: Implementation is an attempt to narrow the gap between the implemented practices and theproposed innovation practices. A curriculum delivery system is made up of interrelated parts thatwork together. A qualitative descriptive research methodology was used to analyze data based oninsights from observations and interviews. The aim of the 2013 curriculum is to foster a goldengeneration of the Indonesian nation through a system that encourages students' effectiveparticipation in the teaching and learning process. It consists of various science-based educationalsubjects and programs offered by the institution. In implementing the 2013 curriculum, it paysgreater attention to three areas, namely forming students who have high morals (affective), skilled(psychomotor), and sustainable insight (cognitive). Thus, it is expected that students will be moreinventive, creative, and productive. The 2013 curriculum aims to produce a superior society in termsof knowledge and technology. Freedom to learn can be interpreted as freedom to think, workindependently, respect change, or adapt. The Merdeka Learning Curriculum seeks to foster a pleasantlearning atmosphere. The aim is to create a positive environment for teachers, students, and parents.Keywords: implementation; 2013 curriculum; Merdeka Belajar curriculumAbstrak: Implementasi adalah upaya untuk mempersempit kesenjangan antara praktik yang diterapkan danpraktik inovasi yang diusulkan. Sebuah sistem penyampaian kurikulum terdiri dari bagian-bagianyang saling berhubungan yang bekerja sama. Metodologi penelitian deskriptif kualitatif digunakanuntuk menganalisis data berdasarkan wawasan dari observasi dan wawancara. Tujuan kurikulum2013 adalah membina generasi emas bangsa Indonesia melalui sistem yang mendorong partisipasiefektif siswa dalam proses belajar mengajar. Ini terdiri dari berbagai mata pelajaran dan programpendidikan berbasis sains yang ditawarkan oleh institusi. Dalam pelaksanaan kurikulum 2013memberikan perhatian lebih besar pada tiga bidang yakni membentuk peserta didik yang bermoraltinggi (afektif), terampil (psikomotorik), dan berwawasan berkelanjutan (kognitif). Dengandemikian, diharapkan siswa akan lebih inventif, kreatif, dan produktif. Kurikulum 2013 bertujuanuntuk menghasilkan masyarakat yang unggul dalam hal pengetahuan dan teknologi. Merdeka Belajardapat diartikan sebagai kebebasan berpikir, bekerja mandiri, menghargai perubahan, ataumenyesuaikan diri. Kurikulum Belajar Merdeka berupaya menumbuhkan suasana belajar yangmenyenangkan. Tujuannya untuk menciptakan lingkungan yang positif bagi guru, siswa, dan orangtua.Kata kunci: Implementasi; Kurikulum 2013; Kurikulum Merdeka Belajar